Coronary calcification among 3477 asymptomatic and symptomatic individuals. (January 2016) - Øvrehus, Kristian A; Jasinskiene, Jurgita; Sand, Niels P; Jensen, Jesper M; Munkholm, Henrik; Egstrup, Kenneth; Lambrecthsen, Jess; Mickley, Hans; Diederichsen, Axel CP
Background: Coronary artery calcification (CAC) can be detected by cardiac computed tomography (CT), is associated to cardiovascular risk, and common in asymptomatic individuals and patients referred for cardiac CT. Design: CAC was evaluated in asymptomatic individuals and symptomatic patients referred for cardiac CT, to assess whether differences in CAC may be explained by symptoms or traditional cardiovascular risk factors. Methods: The presence and extent of CAC, gender, family history of coronary artery disease, hypertension, hyperlipidaemia, diabetes and tobacco were compared in 1220 asymptomatic individuals aged 49–61 years and 2257 age-matched symptomatic patients referred for cardiac CT with suspected coronary artery disease. Results: Symptomatic individuals had a higher frequency of a family history of coronary artery disease (46% vs . 23%, p  < 0.001), hypertension (38% vs . 21%, p  < 0.001), hyperlipidaemia (42% vs . 12%, p  < 0.001), a trend for more diabetes (6% vs . 5%, p  = 0.05), but no significant difference was observed for the presence of CAC (Agatston > 0; 45% vs . 45%, p  = 0.94) or severe calcifications (Agatston > 400; 6% vs . 5%, p  = 0.36). In multivariate analyses age (odds ratio (OR) 1.09–1.18), male gender (OR 3.5–6.43), hypertension (OR 1.42–1.79), hyperlipidaemia (OR 1.86–2.09) and tobacco use (OR 1.83–2.01) were predictors for the presence and extent of CAC, whereas symptoms were not predictive for the presence of (Agatston > 0, OR 0.70 (0.59–0.83)), mild (Agatston ≥ 10; OR 0.85 (0.71–1.02)), moderate (Agatston ≥ 100; OR 0.99 (0.79–1.24)) or severe calcifications (Agatston ≥ 400; OR 0.93 (0.65–1.33)). Conclusion: No difference in the presence or severity of coronary calcifications was observed between asymptomatic and symptomatic middle-aged individuals. After adjusting for cardiovascular risk factors, symptoms were not predictive for the presence or extent of CAC.